2009
DOI: 10.1039/b816112g
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of CHX3(X = F, Cl, Br) with HNO induces remarkable blue shifts of both C–H and N–H bonds

Abstract: The hydrogen-bonded complexes formed from interaction of trihalomethanes CHX(3) (X = F, Cl, Br) with nitrosyl hydride HNO were studied using ab initio MO calculations at the second-order perturbation theory (MP2/6-311++G(d,p)). Each interaction contains at least five separate equilibrium structures. Calculated binding energies range from 4 to 8 kJ mol(-1) with both ZPE and BSSE corrections. While CHBr(3) leads to the most stable complexes with HNO, CHF(3) forms the least stable counterparts. The strength of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
(68 reference statements)
3
16
0
Order By: Relevance
“…The results point out that the C1-H2 bond contraction and its stretching frequency increase in all complexes considered here have a smaller magnitude as compared to those between XCHZ (with Z = O, S; X = CH 3 , H, F, Cl, Br) and HNO at the same MP2/aug-cc-pVTZ level. 50 Indeed, the C1-H2 bond lengths are shortened by 0.0004-0.0018 A ˚and the C1-H2 stretching frequencies are shifted to blue by 11-27 cm À1 (Table 3), whereas the C1-H2 bond length contractions amount to 0.0003-0.0040 A ˚and its corresponding stretching frequencies are shifted by 10-53 cm À1 for XCHZÁ Á ÁHNO. Following complexation, the largest increase of C1-H2 stretching frequency is found in CH 3 CHOÁ Á ÁCO 2 with a value of 27 cm À1 , as compared to that in all remaining XCHOÁ Á ÁCO 2 complexes.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The results point out that the C1-H2 bond contraction and its stretching frequency increase in all complexes considered here have a smaller magnitude as compared to those between XCHZ (with Z = O, S; X = CH 3 , H, F, Cl, Br) and HNO at the same MP2/aug-cc-pVTZ level. 50 Indeed, the C1-H2 bond lengths are shortened by 0.0004-0.0018 A ˚and the C1-H2 stretching frequencies are shifted to blue by 11-27 cm À1 (Table 3), whereas the C1-H2 bond length contractions amount to 0.0003-0.0040 A ˚and its corresponding stretching frequencies are shifted by 10-53 cm À1 for XCHZÁ Á ÁHNO. Following complexation, the largest increase of C1-H2 stretching frequency is found in CH 3 CHOÁ Á ÁCO 2 with a value of 27 cm À1 , as compared to that in all remaining XCHOÁ Á ÁCO 2 complexes.…”
Section: Resultsmentioning
confidence: 97%
“…Both trends discussed above are in line with that of the C-H bond polarization in the XCHO and XCHS isolated monomers, respectively. 49,50 Therefore, we would suggest that the bond contraction and the frequency blue shift of a C-H bond involved in hydrogen bond complexation are mainly determined by its polarization. In particular, the weaker the polarization of a C-H bond acting as proton donor is, the stronger its distance contraction and frequency blue shift as a result of complexation are, and vice versa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have pursued another approach to study the origin of the BSHB and, thereby, a classification of hydrogen bonds, which is rather based on inherent properties of isolated monomers. Implementing this approach, the stability and origin of hydrogen bond involving C‐H covalent bond have been explored . Our theoretical results obtained for the hydrogen‐bonded systems containing C‐H···O/N suggested that the origin of a BSHB in a A‐H···B complex can be probed on the basis of the deprotonation enthalpy (DPE) of the A‐H bond in the isolated proton donor and the proton affinity (PA) of the B atom in the isolated proton acceptor .…”
Section: Introductionmentioning
confidence: 99%
“…[6,9] A creative approach proposes that stability and the origin of blue-shifting H-bond can be explained on the basis of inherent characteristic of the A-H proton donor and the B proton acceptor. [10][11][12] This approach has expanded many studies on looking for the characteristics of both conventional and novel H-bonds. The A and B elements are extended more in the periodic table.…”
Section: Introductionmentioning
confidence: 99%